2018
DOI: 10.9740/mhc.2018.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid–induced hyperammonemia: Incidence, clinical significance, and treatment management

Abstract: Introduction:Valproic acid (VPA)–induced hyperammonemia poses several clinical challenges in psychiatric medicine. The reported incidence of this adverse effect varies widely across the literature. Furthermore, practitioners treat hyperammonemia in asymptomatic patients although studies suggest this practice is unnecessary. The purpose of this study is to evaluate if patients with VPA-induced hyperammonemia are appropriately identified for treatment based on their symptom presentation as well as determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…In most patients, VPA-induced hyperammonemia does not cause encephalopathy; patients are usually asymptomatic and have normal liver function test results. In a study by Baddour et al [13], elevated ammonia levels were not significantly associated with clinical symptoms. In addition, more clinical symptoms were noted in patients with normal ammonia levels.…”
Section: Discussionmentioning
confidence: 87%
“…In most patients, VPA-induced hyperammonemia does not cause encephalopathy; patients are usually asymptomatic and have normal liver function test results. In a study by Baddour et al [13], elevated ammonia levels were not significantly associated with clinical symptoms. In addition, more clinical symptoms were noted in patients with normal ammonia levels.…”
Section: Discussionmentioning
confidence: 87%
“…A review of 24 studies reported that the prevalence of VPA-associated hyperammonemia ranged between 70% and 100% in prospective studies and between 16% and 100% in cross-sectional studies [ 6 ]. One retrospective chart review for 347 patients admitted to a psychiatric unit reported the incidence of VPA-hyperammonemia is about 36%, with 43.2% of those patients with VPA-induced hyperammonemia presenting with symptoms [ 7 ]. This incidence is very close to the 27.8% incidence reported in 158 patients with epilepsy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with delirium may present with inattention, agitation, aggressive behavior or thinking, and disorganized speech, which were the patient's symptoms in this case. It has been reported that valproic acid may induce delirium due to hyperammonemia . In our case, the patient was given Haldol to control delirium and lactulose to reduce serum ammonia.…”
Section: Discussionmentioning
confidence: 87%
“…In adults, the secondary hyperammonemia is more common, especially in the presence of hepatic disorders. It may also happen with normal hepatic function when mitochondrial pathways are interrupted by Reye's syndrome or medications, such as valproic acid, carbamazepine, salicylate, topiramate, or cytotoxic agents . Additionally, renal tubular acidosis, urinary tract dilatation or urinary tract infection, pregnancy, and hypoglycin may contribute to nonhepatic hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%